Novel device for blunt dissection in third space endoscopy: Preliminary animal study (with video) - Yokouchi, Takashi; Masunaga, Teppei; Miyazaki, Kurato; Kato, Motohiko; Fujii, Shota; Momose, Kota; Yamashita, Kotaro; Saito, Takuro; Tanaka, Koji; Yamamoto, Kazuyoshi; Makino, Tomoki; Takahashi, Tsuyoshi; Kurokawa, Yukinori; Eguchi, Hidetoshi; Doki, Yuichiro; Nakajima, Kiyokazu (Endoscopy International Open, 2025)
Blunt dissection is not commonly performed in flexible endoscopic procedures. We developed a novel blunt dissection device and evaluated its feasibility, safety, and potential effectiveness in third space endoscopy procedures.The device consists of a cotton swab and a flexible shaft. To evaluate its functionality, creation of 4-cm submucosal tunnels in live swine stomachs was attempted by either blunt dissection using our device or sharp dissection using a standard monopolar knife. Data on factors such as completion rate, operating time, adverse events, necessity of submucosal injection, and dissected submucosal thickness were collected.Eighteen submucosal tunnels were successfully created (sharp: 9, blunt: 9) by two experienced endoscopists and one novice endoscopist. Median operating time was significantly shorter in the blunt dissection group (239 vs. 429 s, P = 0.008). In the sharp dissection group, the experienced endoscopists did not cause any muscle layer injuries, but the novice endoscopist caused muscle layer injuries in all cases. In the blunt dissection group, neither experienced nor novice endoscopists caused muscle layer injuries. The blunt dissection group required significantly fewer submucosal injections (0 vs. 5, P < 0.001). Median dissected submucosal thickness was similar between the groups.Blunt dissection using our device was feasible, safe, and potentially effective in third space endoscopy procedures by shortening operating time, reducing submucosal injections, and potentially minimizing muscle layer injury.
Keywords: Endoscopy Upper GI Tract; POEM; Endoscopic resection (ESD, EMRc, ...); Endoscopy Lower GI Tract; Endoscopic resection (polypectomy, ESD, EMRc, ...)